Źródła do dziejów szkół dominikanów poznańskich w dobie nowożytnej - Kaczmarek, Krzysztof (Biuletyn Historii Wychowania, 2010)
The present work aims at presenting the most important texts documenting the activity of schools in the St. Dominic Monastery in Poznań in modern times. Following a query carried out in archives, the author made a juxtaposition of relevant texts. It appears that that the most precious monuments shedding light on the Dominican educational system are to be found in Poznań-based archives and registry offices, and in the Archives of the Polish Province of Dominicans in Cracow. The archival material includes documents written by Dominicans, as well as numerous records and documents that provide detailed information on schools operating within the order and on their lecturers and disciples.